2018
DOI: 10.1039/c8nr05072d
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength tailoring of a ZnGa2O4 nanosheet phosphor via defect engineering

Abstract: The multi-wavelength tailoring of ZnGa2O4 nanosheets has been achieved via a defect engineering approach. Controlling the distortion of [GaO6] octahedron and the formation of [GaO4] tetrahedron and oxygen vacancy in ZnGa2O4 lattice can achieve the simultaneous emissions of ultraviolet/blue, green and red wavelengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…Rare earth doped zinc gallate phosphors have been given much interest due to their wide applications in a variety of elds, such as lighting, eld emission display devices (FEDs), and plasma display panels (PDPs). [53][54][55] It contains an optical band gap of the order of 4.4 eV. 56 ZnGa 2 O 4 is known as a self-activated host and it emits blue luminescence without doping any activator ion.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth doped zinc gallate phosphors have been given much interest due to their wide applications in a variety of elds, such as lighting, eld emission display devices (FEDs), and plasma display panels (PDPs). [53][54][55] It contains an optical band gap of the order of 4.4 eV. 56 ZnGa 2 O 4 is known as a self-activated host and it emits blue luminescence without doping any activator ion.…”
Section: Introductionmentioning
confidence: 99%
“…The PersL intensities are weakened as the delay time is prolonged while no peak shift occurs indicating the existence of stable PersL centers. Interestingly, we also found that the PersL of host disappears once Pr 3+ ions are doped in, and this may be due to energy transfer from host to Pr 3+ ions . PersL decay curves of Li 0.995 Ga 5 O 8 :0.005Pr 3+ monitored at 495 nm are also plotted in Figure c.…”
Section: Resultsmentioning
confidence: 67%
“…Figure a presents the PersL spectra of LiGa 5 O 8 as a function of delay times (2, 4, 6, 8, and 10 s) recorded after irradiation by a 254 nm lamp for 60 s, and the powder image detected at the delay time of 2 s is shown in the inset. To our knowledge, the structural defects can also trigger discrete energy levels in the forbidden band, and produce defect‐related luminescence centers . Here, the blue PersL of LiGa 5 O 8 may be ascribed to the self‐activation of Ga‐O in the [Ga2O 4 ] tetrahedra.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…For the O 1s spectrum (Fig. 1d), it can be fitted into two peaks, which correspond to V O (peak at the low energy) and the lattice O (peak at the high energy) [35]. Moreover, the V O peak shifted to higher binding energies and its intensity decreased as Pr 3+ was introduced into the host lattice, indicating that the number of V O decreased.…”
Section: Resultsmentioning
confidence: 93%